Partial agonists of dopamine receptors: clinical effects and dopamine receptor interactions in combining aripiprazole with a full antagonist in treating psychosis. (March 2023) - Cookson, John; Pimm, Jonathan; Reynolds, Gavin
SUMMARY: Partial agonists of dopamine receptors are used in combination with full antagonists in treating psychosis, either to mitigate side-effects or in the hope of increasing effectiveness. We examine how combinations may affect the occupancy of D2 /D3 dopamine receptors and explore how these can explain the outcomes in the light of the dopamine hypothesis of psychosis. The combinations considered here are from published studies combining aripiprazole with amisulpride, with risperidone in people with hyperprolactinaemia and with olanzapine to mitigate weight gain. We discuss possible worsening of symptoms by the addition of a partial agonist or switching. We also examine the potentially adverse interaction with a full antagonist such as haloperidol given during a subsequent relapse to control severe agitation.